Pengaruh Merek Terhadap Minat Beli Roti Jordan Pada PT. Mahakam Megah Mulia - Beatrix Tandirerung, Irham, Mardiana (EKONOMIA, 2018)
The Influence of Brands Against Interest in Buying Jordan Bread at PT. Mahakam MegahMulia. Under the guidance of Mrs. Mardiana as counselor I and Mrs. Beatrix Tandirerung as Counselor II.       The background of this study was to determine the effect of the brand on the interest in buying Jordan bread at PT. Mahakam MegahMulia where consumers see a brand as the most important part of a product, a brand can be a value added in the product and buying interest is part of the behavior component in consuming attitude.       The purpose of this study was to determine the influence of brands on consumer buying interest in Jordan bread PT. Mahakam MegahMulia.       The research method used is an analytical tool that is simple linear regression, based on the results of a simple linear regression analysis, the calculation result is Y = 2.749 + 0.238X, meaning that the function can be explained as follows. The value of positive variable brand regression coefficient means that there is an increase in brand, it will increase interest in buying Jordan brand bread, on the contrary if there is a decline in brand quality, in other words, the rise and fall of buying interest is strongly influenced by the brand.       Note that the Brand variable is 2,287 greater than t table 1,998 and the significance value is 0,026 <a = 0,05. This means that the Brand variable has a significant influence on buying interest with the hypothesis proposed that the brand has a significant effect on interest in buying bread Jordan PT. Mahakam MegahMulia, accepted